2018
DOI: 10.1186/s12199-018-0733-0
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire results on exposure characteristics of pregnant women participating in the Japan Environment and Children Study (JECS)

Abstract: BackgroundThe Japan Environment and Children’s Study (JECS) is a nation-wide birth cohort study investigating environmental effects on children’s health and development. In this study, the exposure characteristics of the JECS participating mothers were summarized using two questionnaires administered during pregnancy.MethodsWomen were recruited during the early period of their pregnancy. We intended to administer the questionnaire during the first trimester (MT1) and the second/third trimester (MT2). The total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 25 publications
0
56
0
Order By: Relevance
“…To our knowledge, this is the first study to examine the prospective relationships between the use of air purifiers and child neurodevelopment using a nationwide birth cohort study dataset (n > 80,000) [17][18][19] while controlling for up to 20 potential confounders. Analysis revealed that adjusted ORs (models 1 and 2) of air-purifier usage for screen-positive cases of developmental delay in the ASQ-3 were significantly lower than the reference (i.e., air-purifier nonuse) in the areas of fine motor and problem solving at 6 months and in communication, fine motor, problem solving, and personal-social at 12 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first study to examine the prospective relationships between the use of air purifiers and child neurodevelopment using a nationwide birth cohort study dataset (n > 80,000) [17][18][19] while controlling for up to 20 potential confounders. Analysis revealed that adjusted ORs (models 1 and 2) of air-purifier usage for screen-positive cases of developmental delay in the ASQ-3 were significantly lower than the reference (i.e., air-purifier nonuse) in the areas of fine motor and problem solving at 6 months and in communication, fine motor, problem solving, and personal-social at 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed design and baseline characteristics of the JECS have been published elsewhere [17][18][19]. Briefly, the JECS is a nationwide, government-funded birth cohort study of various environmental factors and children's health and development.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Consumption of foods was estimated using a food frequency questionnaire on the M-T1 questionnaire [ 36 ]. The frequency of insecticide, herbicide and pesticide use was scored on the M-T1 and M-T2 questionnaires [ 37 ] as no use, 1–3 times a month, 1–6 times a week and every day. The M-T2 questionnaire asked for additional information, i.e., use of a moth repellent for clothes in the closet (never, yes, sometimes and yes, continuously); smoke insecticide indoors (no/yes); and a mosquito coil or electric mosquito repellent mat, a liquid insecticide for maggot and mosquito larva and an herbicide or a gardening pesticide in a garden, balcony or farm (no use, less than once a month, 1–3 times a month, once a week, a few times a week and every day).…”
Section: Methodsmentioning
confidence: 99%
“…Data on the daily use of household pesticides during pregnancy were collected from questionnaires administered between the 2nd and 3rd trimesters (from week 22 to the end of the pregnancy). The classes of pesticides queried in this study are the same as those described in the JECS profile paper [ 20 ]. Specifically, our study evaluated the following pesticide exposures: spraying insecticide indoors (never/less than once a month/1−3 times a month/once a week/a few times a week/everyday), mosquito coil or electric mosquito repellant mats used continuously for more than a few hours (never/less than once a month/1−3 times a month/once a week/a few times a week/everyday), use of liquid insecticides for maggots and mosquito larvae (never/less than once a month/1−3 times a month/once a week/a few times a week/everyday), herbicide or gardening pesticide used for gardens, balcony gardens, or farms (never/less than once a month/1−3 times a month/once a week/a few times a week/everyday), insect repellents sprayed on clothes or applied as skin lotion (never/less than once a month/1−3 times a month/once a week/a few times a week/everyday), moth repellent for clothes in storage (never/sometimes/continuously), and smoke-based insecticide administered indoors (no/yes).…”
Section: Methodsmentioning
confidence: 99%